Trajetórias escolares e sentidos atribuídos à escola entre a tradição e a modernidade: Perfis de jovens açorianos - Ana Matias Diogo (Universidade do Minho, 2016)
In the context of the crisis of youth oppo rtunities a nd individualization processes of contemporary so cieties, the school experience of young people is changing. Lo nger, but also markedly instr umental, based on the recognition of the utility of certificates, and also expressive, to the extent that it is associated to the quest of personal fulfillment. Trends that do not prevent that this exp erience continues to be strongly structured by inequalities. We analyze the case of the Azore s, marked by particularly unfavourable educational indicators. Base d on the analysis of a representative sample of Azorean youngsters, with 15 -34 years, different p rofiles a re identified, in relation to their school pathways and meaning ascribed to school. Along with a ge neral recognition of the va lue ascribed t o schoo l, which crosses the various profiles, we highlig ht the dive rsity of expe riences (more instrumental or more expressive) and the fragility of education pathways of many youngster s, characterized by exclusion, painfulness a nd failure.